TINJAUAN PEMBENTUKAN KABUPATEN MAHAKAM ULU DI PROVINSI KALIMANTAN TIMUR BERDASARKAN UNDANG-UNDANG NOMOR. 32 TAHUN 2004 TENTANG PEMERINTAH DAERAH - Kornelis Kornelis (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTOverview of lifting the title on the Establishment of District Mahakam Ulu In the province of East Kalimantan. Choosing a title as well as the selection of study sites due to the Pros and Cons about splitting the area in West Kutai District, especially in areas that include the Mahakam Ulu, five sub-district (Bagun Long, Long Hubung, Laham, Long and Long Apari Pahangai). From the data obtained Establishment plan Mahakam Ulu district began in 2005 at the Regent Ir.Rama Asian governance and sticking again the Government Regents Ishmael Thomas, SH, M.Si      The aim of the study was to determine the duties and authority of the government in the process of forming a Regional and the extent to which participation in the process of formation masarakat area itself is also to know what are the obstacles in the formation of a region and the last seen of course to add to the scientific treasures the entire academic community of the University August 17, 1945 Samarinda.      The author takes issue on the first initiator division based on Law Number. 32 Year 2004 on a Local Government Act which manages about the formation of a district.